AlCoCrFeNi2.1 composite material coating and preparation method thereof
By introducing Ni3Al particles into AlCoCrFeNi2.1 eutectic high-entropy alloy and preparing coatings using laser cladding technology, the problem of improving wear resistance in the existing technology but difficult to maintain plasticity is solved, and the improvement of hardness and wear resistance is achieved , while maintaining good plasticity.
Patent Information
- Application Number
- CN202411441233.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to maintain good plasticity while improving the wear resistance of AlCoCrFeNi2.1 eutectic high-entropy alloy.
By proportionally proportional and mechanically mixing Ni3Al powder with AlCoCrFeNi2.1 powder, Ni3Al particles-enhanced AlCoCrFeNi2.1 composite material powder was prepared, and a single layer of Ni3Al particles-enhanced AlCoCrFeNi2.1 composite material was prepared by laser cladding technology using laser cladding technology to prepare a single layer of Ni3Al particles-enhanced AlCoCrFeNi2.1 composite material. Coating, adjust the mass fraction of Ni3Al in AlCoCrFeNi2.1 coating to achieve the regulation of tissue structure.
The Ni3Al particle-enhanced AlCoCrFeNi2.1 composite coating has been improved in hardness and wear resistance while maintaining good plasticity. In particular, the AlCoCrFeNi2.1-10Ni3Al composite coating with 10 wt.% Ni3Al particles exhibited optimal hardness and wear resistance.
Smart Images

Figure CN119392240A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a material laser forming technology, in particular to an AlCoCrFeNi 2.1 Composite coating and preparation method thereof, further expanding AlCoCrFeNi 2.1 A method to improve the wear resistance of eutectic high entropy alloys while maintaining good plasticity. Background Art
[0002] In recent years, AlCoCrFeNi with face-centered cubic structure and ordered body-centered cubic structure have been 2.1 Eutectic high entropy alloys have been widely studied, with fracture stress and elongation of 944MPa and 25.6% at room temperature, respectively, which are better than most high entropy alloys and traditional alloys. The alloy's stable structure and excellent comprehensive properties make it the most potential high entropy alloy-based composite material.
[0003] At present, most reinforcements are ceramic particles, which are low in cost, high in hardness and elastic modulus, and can enhance the strength of the alloy, but they sacrifice plasticity to improve hardness. Ni3Al metal reinforcement particles stand out in improving the performance of high entropy alloys. The most important thing is that Ni3Al metal reinforcement particles have both metal plasticity / toughness and ceramic strength / hardness due to the simultaneous existence of metal bonds and covalent bonds, showing good strength and toughness.
[0004] Laser cladding is a surface modification technology. Compared with other conventional surface treatment technologies, it has the advantages of small deformation of the workpiece, high metallurgical bonding strength between the cladding layer and the substrate, high uniformity of the cladding layer, fine grains, and dense structure. It can treat the workpiece locally without affecting the overall performance of the workpiece. It is green and efficient, simple in method, and cost-saving, and has great potential application value. Therefore, Ni3Al particle-reinforced AlCoCrFeNi can be prepared by laser cladding technology. 2.1 Eutectic high entropy alloy coating, to understand the microstructure and performance changes of alloy coating, and further explore the practical application of wear resistance of eutectic high entropy alloy coating Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an AlCoCrFeNi 2.1 Composite material coating and preparation method thereof, Ni3Al powder and AlCoCrFeNi 2.1 The powders were mixed in proportion and mechanically mixed to prepare Ni3Al particle reinforced AlCoCrFeNi 2.1 Composite powder, single-layer Ni3Al particle-reinforced AlCoCrFeNi prepared by laser cladding technology 2.1A composite material coating, by adjusting the content of Ni3Al with different mass fractions, realizes the reinforcement of AlCoCrFeNi by Ni3Al particles 2.1 The microstructure regulation of the composite material improves the hardness and wear resistance of the obtained composite material.
[0006] The technical solution adopted is as follows:
[0007] An AlCoCrFeNi 2.1 composite material coating, including Al, Co, Cr, Fe, Ni and Ni3Al particles, with the molecular formula AlCoCrFeNi 2.1 -xNi3Al; wherein, 0 < x ≤ 10 wt%. Alternatively, the mass fraction of Ni3Al particles in the total mass of AlCoCrFeNi 2.1 and Ni3Al particles is 0 to 10 wt%, and x can be 0 wt%.
[0008] An AlCoCrFeNi 2.1 preparation method of the composite material coating, including the following steps:
[0009] (1) Preparation of the cladding material:
[0010] The metal powder raw materials are prepared according to the molar ratio of Al, Co, Cr, Fe, Ni of 1:1:1:1:2.1, and then Ni3Al particles are added to AlCoCrFeNi 2.1 alloy powder to obtain Ni3Al particle-reinforced AlCoCrFeNi 2.1 composite material powder, and then mechanical mixing is carried out to be used as the cladding powder;
[0011] (2) Preparation of the substrate material:
[0012] The selected hot work die steel is used as the substrate material, the surface of the substrate is polished with sandpaper until smooth, and then ultrasonic cleaning is carried out;
[0013] (3) Laser cladding:
[0014] The cladding powder is pre-placed on the hot work die steel substrate and compacted. During the laser cladding process, an inert gas is always introduced as the protective gas, and Ni3Al metal particle-reinforced AlCoCrFeNi is obtained on the substrate through laser cladding scanning 2.1 composite material coating.
[0015] Preferably, in the step (1), the selected powders of Al, Co, Cr, Fe, Ni have a purity greater than 99.5 wt.%, and an average particle size of 45 μm; the Ni3Al powder has a purity greater than 99.5 wt.%, and an average particle size of 2 μm.
[0016] Preferably, in step (1), the mechanical mixing time is 1 to 2 hours; after mixing, the cladding powder is placed in a vacuum box for drying at a drying temperature of 60 to 100° C. for a drying time of 1 to 6 hours.
[0017] Preferably, in step (2), the hot working abrasive tool steel substrate is polished using sandpaper of types #180, #400, #800, and #1000 in sequence, and after polishing, is placed in alcohol for ultrasonic cleaning, and the cleaning time is 20 to 40 minutes.
[0018] Preferably, in step (2), the ultrasonic cleaning is followed by drying in a vacuum oven at a temperature of 80 to 100° C. for a drying time of 2 to 6 hours.
[0019] Preferably, in step (3), the inert gas is argon, and the flow rate of the argon is 2 to 6 L / min; as a further preference, the flow rate is 5 L / min.
[0020] Preferably, in step (3), the thickness of the cladding powder pre-placed on the hot-working abrasive steel substrate is 0.5 to 2 mm; as a further preference, the thickness is 1 mm.
[0021] Preferably, in step (3), the laser cladding scanning speed is 3 to 8 mm / s, and the spot diameter is 3 to 5 mm; as a further preference, the laser cladding scanning speed is 5 mm / s, and the spot diameter is 3 mm.
[0022] Preferably, in step (3), the laser power is 800-1500W.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention adopts Ni3Al particles as reinforcement and adopts laser cladding method to obtain Ni3Al particle reinforced AlCoCrFeNi 2.1 Composite coating, adjusting Ni3Al in AlCoCrFeNi 2.1 The mass fraction in the coating makes the composite material coating evenly distributed on the substrate surface, improves the bonding strength between the coating and the substrate, and thus improves the hardness and wear resistance of the formed cladding layer.
[0025] The present invention obtains Ni3Al metal particle reinforced AlCoCrFeNi by laser cladding method 2.1 Composite material coating, high density and fine structure, evenly distributed. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a comparison of the macroscopic morphologies of the coatings prepared in Example 1 under different process parameters.
[0027] Figure 2 The cross-sectional morphology (left figure) and line analysis results (right figure) of the coating prepared in Example 1 under different process parameters.
[0028] Figure 3 AlCoCrFeNi prepared in Examples 2 to 6 2.1 Scanning electron microscope (SEM) image of the -xNi3Al composite coating.
[0029] Figure 4 AlCoCrFeNi prepared in Examples 2 to 6 2.1 -Hardness of xNi3Al composite coatings.
[0030] Figure 5 The H13 matrix and the AlCoCrFeNi prepared in Example 2-6 2.1 -Comparison of friction coefficients of xNi3Al composite coatings.
[0031] Figure 6 The H13 matrix and the AlCoCrFeNi prepared in Example 2-6 2.1 -xNi3Al composite coating wear volume comparison.
[0032] Figure 7 The H13 matrix and the AlCoCrFeNi prepared in Example 2-6 2.1 -xNi3Al composite coating microstructure image comparison after wear. DETAILED DESCRIPTION
[0033] The accompanying drawings are only used for illustrative purposes. The technical solution of the present invention is further described below in conjunction with specific embodiments and the accompanying drawings, in which some prior arts or common knowledge may be omitted.
[0034] Example 1
[0035] A kind of AlCoCrFeNi 2.1 The method for preparing a composite material coating comprises the following steps:
[0036] ① Preparation of alloy powder:
[0037] High-purity Al, Co, Cr, Fe, and Ni powders (greater than 99.5wt.%, with an average particle size of 45μm) were selected as raw materials, and the alloy powders were prepared in an atomic ratio of 1:1:1:1:2.1, and mechanically mixed for 1h. 2.1 The powder was placed in a vacuum drying oven at 100 °C for 1 h to remove excess moisture.
[0038] ②Matrix material:
[0039] H13 hot-working abrasive steel with a size of 40 mm × 15 mm × 10 mm was selected, and the substrate surface was first polished with sandpaper of types #180, #400, #800, and #1000 until it was smooth, then ultrasonically cleaned in alcohol, and finally placed in a vacuum drying oven at 100 °C for 1 hour like the cladding material to remove excess moisture.
[0040] ③Laser cladding:
[0041] AlCoCrFeNi 2.1 The alloy powder was pre-placed on the H13 substrate and compacted to a thickness of 1.0 mm. During the laser cladding process, high-purity argon was always introduced as a protective gas to prevent surface oxidation of the cladding material. The Ar gas flow rate was 5 L / min, and the parameters in Table 1 were used as laser parameters for single-layer laser cladding.
[0042] Table 1 Laser power and scanning speed used in Example 1
[0043]
[0044]
[0045] The AlCoCrFeNi obtained in Example 1 2.1 The macroscopic morphology of the alloy coating samples was observed, and the cross-sectional morphology and line analysis from the cladding layer to the substrate were performed. The results are shown in Figure 1 , Figure 2 As shown. Figure 1 It can be observed that the surface of the cladding layer of sample VI is smooth and shiny, the alloy powder is fully melted and completely spread, and shows uniform width and height, indicating that the parameters of laser power 1500W and scanning speed 5mm / s are suitable for the cladding work of high entropy alloy coating. Figure 2 It can also be seen from the cross-sectional morphology and line analysis diagram that the powder and the matrix are well combined.
[0046] Example 2
[0047] A kind of AlCoCrFeNi 2.1 The method for preparing a composite material coating comprises the following steps:
[0048] ① Preparation of alloy powder:
[0049] High-purity Al, Co, Cr, Fe, and Ni powders (greater than 99.5wt.%, with an average particle size of 45μm) were selected as raw materials, and the alloy powders were prepared in an atomic ratio of 1:1:1:1:2.1, and mechanically mixed for 1h. 2.1The powder was placed in a vacuum drying oven at 100 °C for 1 h to remove excess moisture.
[0050] ②Matrix material:
[0051] H13 hot-working abrasive steel with a size of 80 mm × 15 mm × 10 mm was selected, and the substrate surface was first polished with sandpaper of types #180, #400, #800, and #1000 until it was smooth, then ultrasonically cleaned in alcohol, and finally placed in a vacuum drying oven at 100 °C for 1 hour like the cladding material to remove excess moisture.
[0052] ③Laser cladding
[0053] AlCoCrFeNi 2.1 The alloy powder was pre-placed on the H13 substrate and compacted to a thickness of 1.0 mm. During the laser cladding process, high-purity argon was always introduced as a protective gas to prevent surface oxidation of the cladding material. The Ar gas flow rate was 5 L / min, and the laser cladding parameters were selected as a scanning speed of 5 mm / s, a laser power of 1500 W, and a spot diameter of 3 mm for single-layer laser cladding.
[0054] Example 3
[0055] 2.5wt.% Ni3Al powder (greater than 99.5wt.%, average particle size 2μm) was added to the mixed AlCoCrFeNi 2.1 Eutectic high entropy alloy powder was mechanically mixed for 1 hour, and then the obtained AlCoCrFeNi 2.1 -2.5Ni3Al composite material powder was placed in a vacuum drying oven at 100°C for 1 hour to remove excess moisture. Other steps and specific methods were the same as in Example 1.
[0056] Example 4
[0057] 5.0wt.% Ni3Al powder (greater than 99.5wt.%, average particle size 2μm) was added to the mixed AlCoCrFeNi 2.1 Eutectic high entropy alloy powder was mechanically mixed for 1 hour, and then the obtained AlCoCrFeNi 2.1 The -5.0NbC composite material powder was placed in a vacuum drying oven at 100°C for 1 hour to remove excess moisture. The other steps and specific methods were the same as those in Example 1.
[0058] Example 5
[0059] 7.5wt.% Ni3Al powder (greater than 99.5wt.%, average particle size 2μm) was added to the mixed AlCoCrFeNi 2.1 Eutectic high entropy alloy powder was mechanically mixed for 1 hour, and then the obtained AlCoCrFeNi2.1 The -7.5Ni3Al composite powder was placed in a vacuum drying oven at 100 °C for 1 h to remove excess moisture. Other steps and specific methods were the same as those in Example 1.
[0060] Example 6
[0061] 10 wt.% of Ni3Al powder (greater than 99.5 wt.%, average particle size of 2 μm) was added to the uniformly mixed AlCoCrFeNi 2.1 eutectic high - entropy alloy powder, and mechanical mixing was carried out for 1 h. Then the obtained AlCoCrFeNi 2.1 -10Ni3Al composite powder was placed in a vacuum drying oven at 100 °C for 1 h to remove excess moisture. Other steps and specific methods were the same as those in Example 1.
[0062] The AlCoCrFeNi 2.1 alloy coatings of Examples 2 - 6 and the AlCoCrFeNi 2.1 -xNi3Al composite coatings at different Ni3Al contents were tested by scanning electron microscopy (SEM) to characterize the microstructural morphology of the alloy coatings. The results are shown in Figure 3 , where Figures (a) - (e) are the composite coatings prepared in Examples 2, 3, 4, 5, and 6 respectively. It can be seen that: the AlCoCrFeNi 2.1 coating without Ni3Al addition showed typical equiaxed grains. After adding Ni3Al, the coating changed to dendritic grains (0 < x ≤ 7.5) and then to a two - phase lamellar structure (x = 10). The AlCoCrFeNi 2.1 -xNi3Al (0 ≤ x ≤ 7.5) composite coatings were all composed of three phases (represented by letters A, B, and C in the figure), namely Ll2 phase (A), FCC phase (B), and BCC phase (C). With the increase of Ni3Al content, the Ll2 phase first decreased rapidly and then increased; the BCC phase first increased and then decreased. When 10 wt.% Ni3Al was added, the BCC phase disappeared, and the AlCoCrFeNi 2.1 -10Ni3Al composite coating was composed of Ll2 and FCC two phases.
[0063] The AlCoCrFeNi 2.1 alloy coatings of Examples 2 - 6 and the AlCoCrFeNi 2.1 -xNi3Al composite coatings at different Ni3Al contents were tested for Vickers microhardness. Along the longitudinal section of the clad sample, from the top layer of the clad layer to the substrate, a point was tested every 0.1 mm. The results are shown in Figure 4 . The results show that the average hardness of the H13 steel substrate material is 196 HV0.5, and the AlCoCrFeNi without Ni3Al addition2.1 The average hardness of the coating reached 270HV0.5, which was 37.8% higher than that of the substrate. The hardness of the coating increased significantly after adding Ni3Al, and the hardness of the coating with 10wt.% Ni3Al was as high as 425HV0.5, which was 57.4% higher than that of the coating without Ni3Al.
[0064] For H13 matrix material, AlCoCrFeNi 2.1 Alloy coating and AlCoCrFeNi with different Ni3Al contents in Examples 3-6 2.1 -xNi3Al composite coating was tested for wear resistance, and the results are shown in Figure 5 The results show that: H13 matrix, AlCoCrFeNi 2.1 The average friction coefficients of the alloy coating, the composite coating with 2.5wt.%, 5.0wt.%, 7.5wt.%, and 10wt.% Ni3Al added are approximately 1.0, 0.9, 0.7, 0.53, 0.68, and 0.51, respectively. It can be seen that AlCoCrFeNi 2.1 The friction coefficient of the -xNi3Al coating is lower than that of the H13 substrate. In addition, the addition of Ni3Al particles can reduce the friction coefficient of the AlCoCrFeNi 2.1 - Friction coefficient of the xNi3Al coatings. Among them, the average friction coefficient of the coatings with 5.0wt.% and 10wt.% Ni3Al particles added showed the lowest.
[0065] Figure 6 H13 matrix, AlCoCrFeNi 2.1 Alloy coating and AlCoCrFeNi 2.1 Wear volume of -xNi3Al coating. AlCoCrFeNi 2.1 Alloy coating and AlCoCrFeNi 2.1 The wear volumes of the -xNi3Al (x=2.5, 5.0, 7.5, 10wt.%) eutectic high entropy alloy-based composite coatings are 3.08×10 7 μm 3 , 2.50×10 7 μm 3 ,7.27×10 6 μm 3 , 1.04×10 7 μm 3 , 6.50×10 6 μm 3 As the Ni3Al content increases, the wear volume of the coating decreases. Among them, the coating with 10wt.% Ni3Al has the smallest wear volume (6.5×106 μm 3 ), which is 2.05×10 7 μm 3 Reduced by 3 times.
[0066] Figure 7 H13 matrix (a), AlCoCrFeNi 2.1 Alloy coating (b) and AlCoCrFeNi 2.1 -xNi3Al coating after wear surface morphology of the wear scar, wherein (c)-(f) corresponds to the AlCoCrFeNi of Examples 3-6, respectively. 2.1 -xNi3Al coating. It can be seen that: H13 matrix and AlCoCrFeNi 2.1 There are many plowing grooves parallel to the friction direction on the wear scar surface of the alloy coating, which is a typical abrasive wear morphology. With the increase of Ni3Al content, AlCoCrFeNi 2.1 A large amount of black oxide peeling layer was produced on the worn surface of the -xNi3Al (x>2.5) composite coating, and no obvious plowing marks were found, which indicates that the wear resistance of the coating increased after adding Ni3Al.
[0067] In summary, the present invention provides a Ni3Al metal particle reinforced AlCoCrFeNi 2.1 Coating and preparation method thereof: By adjusting the Ni3Al content with different mass fractions, a single-layer Ni3Al particle-reinforced AlCoCrFeNi 2.1 Composite coating realizes close bonding between particle reinforcement and eutectic high entropy alloy, making the coating highly dense, finely structured and high hardness, further improving AlCoCrFeNi 2.1 Wear resistance of eutectic high entropy alloy. In particular, AlCoCrFeNi with 10wt.% Ni3Al particle reinforcement 2.1 -10Ni3Al composite coating has the best hardness and wear resistance.
[0068] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. AlCoCrFeNi 2.1 A composite material coating, characterized in that Includes Al, Co, Cr, Fe, Ni and Ni3Al particles, with the molecular formula AlCoCrFeNi 2.1 -xNi3Al; where 0 <x≤10wt%。 2. An AlCoCrFeNi as claimed in claim 1 2.1 A method for preparing a composite material coating, characterized in that: The steps include: (1) Cladding material preparation: The metal powder raw materials were prepared according to the molar ratio of Al, Co, Cr, Fe, and Ni of 1:1:1:1:2.1, and then Ni3Al particles were added to AlCoCrFeNi 2.1 Alloy powder, thus obtaining Ni3Al particle reinforced AlCoCrFeNi 2.1 Composite material powder, which is then mechanically mixed as cladding powder; (2) Preparation of base materials: The selected hot-working abrasive steel is used as the base material, the base surface is polished with sandpaper until it is smooth, and then ultrasonic cleaning is performed; (3) Laser cladding: The cladding powder is pre-placed on the hot-working abrasive steel substrate and compacted. During the laser cladding process, an inert gas is always introduced as a protective gas. The Ni3Al metal particle reinforced AlCoCrFeNi 2.1 Composite coating.
3. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (1), the purity of the selected Al, Co, Cr, Fe, and Ni powders is greater than 99.5wt.%, and the average particle size is 45μm; the purity of the Ni3Al powder is greater than 99.5wt.%, and the average particle size is 2μm.
4. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (1), the mechanical mixing time is 1 to 2 hours; after mixing, the cladding powder is placed in a vacuum box for drying at a drying temperature of 60 to 100° C. for a drying time of 1 to 6 hours.
5. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (2), the hot-working abrasive tool steel substrate is polished with sandpaper of types #180, #400, #800, and #1000 in sequence, and then ultrasonically cleaned in alcohol for 20 to 40 minutes.
6. An AlCoCrFeNi according to claim 5 2.1 A method for preparing a composite material coating, characterized in that: In the step (2), the ultrasonic cleaning is followed by drying in a vacuum box at a temperature of 80 to 100° C. for a drying time of 2 to 6 hours.
7. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (3), the inert gas is argon, and the flow rate of the argon is 2 to 6 L / min.
8. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (3), the thickness of the cladding powder pre-placed on the hot working abrasive tool steel substrate is 0.5 to 2 mm.
9. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (3), the laser cladding scanning speed is 3 to 8 mm / s, and the spot diameter is 3 to 5 mm.
10. An AlCoCrFeNi according to claim 2 2.1 A method for preparing a composite material coating, characterized in that: In the step (3), the laser power is 800 to 1500W.